Wheat Production Alters Soil Microbial Profiles and Enhances Beneficial Microbes in Double-Cropping Soybean - Rocha, Leonardo F.; Bond, Jason P.; Fakhoury, Ahmad M. (Frontiers in Agronomy, 2022)
Plant-parasitic nematodes represent a substantial constraint on global food security by reducing the yield potential of all major crops. The soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) is widely distributed across major soybean production areas of the U.S., being the major soybean yield-limiting factor, especially in the Midwestern U.S. Double cropped (DC) soybean is commonly planted following winter wheat. We previously reported double-cropping soybean fields with reduced SCN counts compared to fallow at both R1 growth stage (beginning of flowering) (-31.8%) and after soybean harvest (-32.7%). To test if higher counts of beneficial and SCN antagonistic microorganisms could be correlated with the suppression of SCN in fields previously planted with wheat, three field locations with noted SCN suppression were selected for a metagenomics study. Ten subplots were selected (5 wheat and 5 fallow pre-soybean) from each location. A total of 90 soil samples were selected: 3 fields x 2 treatments x 3 timepoints x 5 replications. Three DNA markers targeted distinct microbial groups: bacteria (16S V4-V5), fungi (ITS2), and Fusarium (tef1). Amplicons were sequenced using an Illumina MiSeq platform (300 bp paired-end). Sequencing datasets were processed in R using the DADA2 pipeline. Fungal communities differed significantly between DC and fallow plots at soybean planting and after harvest (P<0.001). Fungal populations were affected by location in all sampling times and by treatments before planting and after soybean harvest. Several enriched fungal and bacterial taxa in wheat plots, including Mortierella, Exophiala, Conocybe, Rhizobacter spp. and others, were previously reported to parasitize SCN and other plant-parasitic nematodes, suggesting a potential role of beneficial microbes in suppression of SCN in soybean fields double-cropped with wheat.